Problemática en la ejecución de sentencias de la Corte Interamericana de Derechos Humanos. El caso peruano - Castañeda Otsu, Susana Ynes (Revista de Derecho, 2019)
Peru has been the object of 28 judgments of conviction by the Inter-American Court of Human Rights, what makes it the member country with the largest number of these sentences. To date, it has complied with complete reparations in only two cases. The author analyses the type of reparations ordered in the sentences, and the causes of the high level of non-compliance. Finally, she makes offers of modification to the specific regulation on the matter, unification of the jurisprudence on the part of the Penal Rooms of the Supreme Court, between others, to solve partly detected problematic, although the Peruvian State has the obligation to comply with the Court judgments on having had accepted his contentious jurisdiction.